Optical system design of artificial compound eye based on field stitching. Issue 6 (30th March 2017) - Wang, Yuwei; Cai, Bolin; Lu, Yu; Chen, Xiangcheng; Wang, Keyi
ABSTRACT: This paper presents an optical system design method for artificial compound eye (ACE) to realize large field‐of‐view (FOV) and high‐resolution imaging. The designed ACE is actually a multi‐aperture optical system which comprises layering cameras mounted over a hemisphere. Cameras are layered based on the field stitching principle, such that images captured by them can combine with each other to form a panoramic image. The design guidelines enable the construction of ACEs with arbitrary FOVs. In the experiment, an ACE consisting of seven cameras was fabricated with a spherical shell of radius 4 cm. Then a panoramic image with 75° FOV and 18 million pixels was obtained that demonstrated the validity of the proposed method. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1277–1279, 2017